Comparative Genomic Analysis of Two Clonally Related Multidrug Resistant Mycobacterium tuberculosis by Single Molecule Real Time Sequencing - Leung, Kenneth Siu-Sing; Siu, Gilman Kit-Hang; Tam, Kingsley King-Gee; To, Sabrina Wai-Chi; Rajwani, Rahim; Ho, Pak-Leung; Wong, Samson Sai-Yin; Zhao, Wei W.; Ma, Oliver Chiu-Kit; Yam, Wing-Cheong (Frontiers in Cellular and Infection Microbiology, 2017)
Background: Multidrug-resistant tuberculosis (MDR-TB) is posing a major threat to global TB control. In this study, we focused on two consecutive MDR-TB isolated from the same patient before and after the initiation of anti-TB treatment. To better understand the genomic characteristics of MDR-TB, Single Molecule Real-Time (SMRT) Sequencing and comparative genomic analyses was performed to identify mutations that contributed to the stepwise development of drug resistance and growth fitness in MDR-TB under in vivo challenge of anti-TB drugs. Result: Both pre-treatment and post-treatment strain demonstrated concordant phenotypic and genotypic susceptibility profiles towards rifampicin, pyrazinamide, streptomycin, fluoroquinolones, aminoglycosides, cycloserine, ethionamide and para-aminosalicylic acid. However, although both strains carried identical missense mutations at rpoB S531L, inhA C-15T and embB M306V, MYCOTB Sensititre assay showed that the post-treatment strain had 16-, eight- and four-fold elevation in the minimum inhibitory concentrations (MICs) towards rifabutin, isoniazid and ethambutol respectively. The results have indicated the presence of additional resistant-related mutations governing the stepwise development of MDR-TB. Further comparative genomic analyses have identified three additional polymorphisms between the clinical isolates. These include a single nucleotide deletion at nucleotide position 360 of rv0888 in pre-treatment strain, and a missense mutation at rv3303c (lpdA) V44I and a 6-bp inframe deletion at codon 67-68 in rv2071c (cobM) in the post-treatment strain. Multiple sequence alignment showed that these mutations were occurring at highly conserved regions among pathogenic mycobacteria. Using structural-based and sequence-based algorithms, we further predicted that the mutations potentially have deleterious effect on protein function. Conclusion: This is the first study that compared the full genomes of two clonally-related MDR-TB clinical isolates during the course of anti-TB treatment. Our work has demonstrated the robustness of SMRT Sequencing in identifying mutations among MDR-TB clinical isolates. Comparative genome analysis also suggested novel mutations at rv0888, lpdA and cobM that might explain the difference in antibiotic resistance and growth pattern between the two MDR-TB strains.